A non-centrosymmetric chalcohalide synthesized through the combination of chemical tailoring with aliovalent substitution. Issue 22 (27th February 2023) - Song, Yufei; Qian, Zhen; Zhou, Boru; Yu, Hongwei; Hu, Zhanggui; Wang, Jiyang; Wu, Yicheng; Wu, Hongping
Abstract : A new chalcohalide, [Sr4 Cl2 ][Ge3 S9 ], was synthesized through chemical tailoring and aliovalent substitution strategies. Abstract : A new non-centrosymmetric (NCS) chalcohalide, [Sr4 Cl2 ][Ge3 S9 ], was successfully designed and synthesized through combining chemical tailoring with aliovalent substitution strategies from the maternal [NaSr4 Cl][Ge3 S10 ]. It can exhibit a large SHG effect (0.97 × AgGaS2 ), a wide band gap of 3.71 eV, and a high LDT (∼16 × AgGaS2 ). These results indicate that [Sr4 Cl2 ][Ge3 S9 ] may be a potential infrared nonlinear optical crystal.